Immune response to allergens in sheep sensitized to house dust mite - Velden Joanne; Snibson Ken J; Bischof Robert J; Meeusen Els NT (BMC, 2008)
Abstract Background House dust mite (HDM) allergens are a major cause of allergic asthma. Most studies using animal models of allergic asthma have used rodents sensitized with the 'un-natural' allergen ovalbumin. It has only recently been recognized that the use of animal models based on HDM provide a more relevant insight into the allergen-induced mechanisms that underpin human allergic disease. We have previously described a sheep model of human allergic asthma that uses Dermatophagoides pteronyssinus HDM. The present study extends our understanding of the immune effects of HDM and the allergens Der p 1 and Der p 2 in the sheep model of asthma. Methods Peripheral blood sera from non-sensitized (control) sheep and sheep sensitized to HDM was collected to determine immunoglobulin (Ig) reactivities to HDM, Der p 1 and Der p 2 by ELISA. Bronchoalveolar lavage (BAL) fluid collected following allergen challenge was also assessed for the presence of HDM-specific antibodies. To examine the cellular immune response to HDM allergens, T cell proliferation and cutaneous responses were assessed in sensitized and control sheep. Results Strong HDM- and Der p 1-specific IgE, IgG1, IgG2 and IgA serum responses were observed in sensitized sheep, while detectable levels of HDM-specific IgG1 and IgA were seen in BAL fluid of allergen-challenged lungs. In contrast, minimal antibody reactivity was observed to Der p 2. Marked T cell proliferation and late phase cutaneous responses, accompanied by the recruitment of eosinophils, indicates the induction of a cellular and delayed-type hypersensitivity (DTH) type II response by HDM and Der p 1 allergen, but not Der p 2. Conclusion This work characterizes the humoral and cellular immune effects of HDM extract and its major constituent allergens in sheep sensitized to HDM. The effects of allergen in HDM-sensitized sheep were detectable both locally and systemically, and probably mediated via enzymatic and immune actions of the major HDM allergen Der p 1. This study extends our understanding of the actions of this important allergen relevant to human allergic asthma and its effects in sheep experimentally sensitized to HDM allergens.